Anton's dance class - Du Beke, Anton (United Kingdom Kyle Cathie Limited, 2007)
For each of the five Ballroom dances and five Latin dances, Anton describes the history and origins of the dance, and illustrates his pithy text with step-by-step photography and glorious action shots from the past. He then gives easy-to-follow instruction to help you do those steps at home or in dance class. And this is all captured on a dynamic DVD too, demonstrating the steps of four of the individual dances
Foreword by Len Goodman -- Introduction -- The bits before you move -- The Foxtrot -- The Rumba -- The Waltz -- The Cha cha cha -- The Tango -- The Paso doble -- The Quickstep -- The Samba -- The Viennese waltz -- The Jive
with a foreword by Len Goodman
CHK-1016g Donated by Tom Pena
Keywords: Ballroom dancing -- Technique